2016
DOI: 10.1111/dmcn.13046
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from studying the functional impact of adaptive seating interventions for children with cerebral palsy

Abstract: Little empirical evidence exists about the effectiveness of assistive technology interventions for children with cerebral palsy (CP) to inform clinical practice. This article reviews what we know about the functional impact of adaptive seating interventions -a common assistive technology type recommended for children with CP. A contemporary assistive technology outcomes framework is considered as a way to model the temporality and measure the effects of seating interventions and moderating cofactors. Three res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…The environment involves family empowerment and the application of assistive devices, such as adaptive seating systems and power mobility. These assistive devices may help the infant in its discovery of the world and its interaction with other people, thereby promoting cognitive and personal development . We have summarized our suggestions for future research in Appendix S3 (online supporting information).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environment involves family empowerment and the application of assistive devices, such as adaptive seating systems and power mobility. These assistive devices may help the infant in its discovery of the world and its interaction with other people, thereby promoting cognitive and personal development . We have summarized our suggestions for future research in Appendix S3 (online supporting information).…”
Section: Discussionmentioning
confidence: 99%
“…These assistive devices may help the infant in its discovery of the world and its interaction with other people, thereby promoting cognitive and personal development. [98][99][100][101] We have summarized our suggestions for future research in Appendix S3 (online supporting information). fonds, Phelps Stichting, Revalidatie Nederland and the Nederlands Vereniging van Revalidatieartsen.…”
Section: Conclusion and Suggestions For Future Researchmentioning
confidence: 99%
“…15 Cihazlarla ilgili maliyet, çeşitlilik, etkinlik, memnuniyet konusundaki belirsizlikler SP'li çocuklara AC önerisinde bulunmak için güçlü kanıtlar sunmamaktadır. 16…”
Section: Introductionunclassified
“…They concluded however that seating provision is complex and practitioners are advised to find out what is meaningful and important for children and their families when considering outcomes (Stier et al, 2016). These studies provide informative findings which consider the impact that adaptive seating may have on everyday functioning for children with cerebral palsy, however the evidence base remains limited (Novak et al, 2013;Ryan, 2016). Hammel et al (2013) explored the perceptions of adults who use adaptive seating and found that they are viewed as helpful to enhance choice, control and social integration.…”
mentioning
confidence: 99%
“…There is recognition that research regarding seating and children with cerebral palsy should be co-developed with people who use such equipment so as to better understand their perspectives (Ryan, 2016). Therefore it is important to understand the views of children with cerebral palsy and their parents who use seating systems.…”
mentioning
confidence: 99%